The modified Nadeem’s technique for the treatment of H-type tracheoesophageal fistula - Zahra, Fatima Al; Akhtar, Nadeem; Khan, Sana; Abdullah Saif, Mohammed Abdulmomen; Butt, Muhammad Umair; Syed, Ramsha (International Journal of Contemporary Pediatrics, 2021)
An H-type fistula is an unusual category of the tracheoesophageal fistula to occur constituting only 5 % of all cases. The continuity of the esophagus leads to a delayed and vague presentation with a complaint of choking on feed and respiratory issues unlike the inability to feed and frothing soon after birth in other variants of tracheoesophageal fistula. We received a referred case of a 3-months-old male having recurrent respiratory tract infections and episodes of choking. After a thorough evaluation, a suspicion of H-type fistula was encountered that led to refined radiological evaluation. Contrast given per oral also delineated fistula and CT scan with intravenous and oral contrast revealed fistulous communication between two channels. Operated for H-type fistula through the modified Nadeem’s technique via a left cervical approach and discharged after uneventful recovery. The modified Nadeem’s technique via a left-sided cervical approach facilitates access, vision, and intervention easily as compared to the conventional right-sided approach given in the literature.